Embodying Transnational Yoga: Eating, Singing, and Breathing in Transformation - Miller, Christopher Patrick (Routledge Series on the Indian Ocean and Trans-Asia Series, 2023)
Cover -- Endorsement Page -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of Figures -- Preface -- Acknowledgements -- Note on Transliteration and Names -- Introduction: Engaged Alchemies: New Approaches to the Study of Contemporary Yoga -- What Is Yoga? -- Modern Yoga Studies -- Studying Transnational Yoga Cultures -- Botanical Metaphors, Frictions, and Mobilities -- Embodying Transnational Yoga -- Eating, Singing, and Breathing in Transformation -- Worlding the Indian Ocean -- Distinct Gurus, Distinct Ways of Knowing -- Notes -- References -- Chapter 1: Patanjali and Arjuna meet American Countercuisine: Yogic Diet and Selfless Service at Gurani Anjali's Yoga Anand Ashram, Long Island -- Food in the Study of Religion -- Studying Yogic Foodways: Semiotic, Historical, and Culturalist Approaches -- Amityville's Heritage Meets Urbanization, Immigration, and the American Counterculture -- Amityville Turns East -- Gurani Anjali's Yoga Anand Ashram, established 1972 -- Food Justice: American Countercuisine and Hip Enterprise Movements -- American Countercuisine and Hip Enterprises -- Santosha Vegetarian Dining, Plus… -- Conclusion: Anjali's Yogic Internationalism -- Notes -- References -- Chapter 2: Yogananda's Sacred Music in Paradise: Ukuleles and the Unstruck Sound at Polestar Gardens, Hawaii -- Studying Music and Instruments -- Colonial Encounters: Indian Music, anāhata-nāda, and Harmoniums -- Music in Colonial India -- Yogananda's Musicological Inheritance -- Yogananda's Music in the Early Twentieth-Century United States -- The "unstruck sound": anāhata-nāda -- Yogananda's Harmonium: An (in?)Authentic Bridge to the Unstruck Sound -- Polestar Gardens: Puna District's Kı̄rtan Paradise -- Kı̄rtan at Polestar Gardens: Harmoniums and Ukuleles Transport us to the Internal Sound.